The First Armenians In America During The Colonial Period - Avakian, Knarik (ՀՀ ԳԱԱ)
It is difficult to determine the exact number of Armenians emigrated to America during the given period of British colonialism, since no documents have been preserved about the registration of newcomers, including that of the Armenians, till 1820. It should be noted that the settlement of these few Armenians in America at this period is not connected with the intentional emigration to USA from the various Armenian-inhabited regions in the subsequent years; they were merely individuals outside the main stream of emigrants.
Keywords: Հայագիտություն; Հայոց պատմություն; Պատմություն; Հայոց ցեղասպանություն (1915); Հայագիտական ժառանգություն; Հնագիտություն և ազգագրություն; Փիլիսոփայություն և իրավունք; Արվեստ և ճարտարապետություն; Ժողովրդագրություն և կառավարում